2006
DOI: 10.1038/sj.bjc.6602919
|View full text |Cite
|
Sign up to set email alerts
|

Refining the role of laparoscopy and laparoscopic ultrasound in the staging of presumed pancreatic head and ampullary tumours

Abstract: Laparoscopy and laparoscopic ultrasound have been validated previously as staging tools for pancreatic cancer. The aim of this study was to identify if assessment of vascular involvement with abdominal computed tomography (CT) would allow refinement of the selection criteria for laparoscopy and laparoscopic ultrasound (LUS). The details of patients staged with LUS and abdominal CT were obtained from the unit's pancreatic cancer database. A CT grade (O, A-F) of vascular involvement was recorded by a single radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…As a result several groups recommend diagnostic laparoscopy in combination with or without laparoscopic ultrasonography as a standard procedure in the staging of all patients with resectable as well as unresectable pancreatic cancer. [9,10] However recent studies using high quality CT-scanning in resectable pancreatic cancer patients revealed that only a small percentage of these patients would benefit from a routine diagnostic laparoscopy. [11,12] …”
Section: Introductionmentioning
confidence: 99%
“…As a result several groups recommend diagnostic laparoscopy in combination with or without laparoscopic ultrasonography as a standard procedure in the staging of all patients with resectable as well as unresectable pancreatic cancer. [9,10] However recent studies using high quality CT-scanning in resectable pancreatic cancer patients revealed that only a small percentage of these patients would benefit from a routine diagnostic laparoscopy. [11,12] …”
Section: Introductionmentioning
confidence: 99%
“…80% of articles extracted were review articles, whilst the remaining did not assess SL/LUS as staging modality. Of the remaining 41 articles, 12 studies did not satisfy the eligibility criteria; 22 were for potentially resectable PPC and 7 for PBC [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37] (Supplemental information, Table ST1 to attain pneumoperitoneum and were therefore excluded from our analysis. Therefore, a total of 2,827 patients with PPC and 478 patients with PBC, deemed potentially resectable on preoperative staging, were included for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the results of these studies have suggested that LUS may improve the sensitivity to detect liver metastases. [9][10][11][12][13][14][15] Few studies have investigated the additional value of LUS compared to modern preoperative imaging modalities. However, study cohorts were small (n < 50), and only few patients were diagnosed with occult distant disease (one and two cases, respectively).…”
Section: Discussionmentioning
confidence: 99%